Zoledronic acid inhibits NFAT and IL-2 signaling pathways in regulatory T cells and diminishes their suppressive function in patients with metastatic cancer. (3rd August 2017) - Sarhan, Dhifaf; Leijonhufvud, Caroline; Murray, Shannon; Witt, Kristina; Seitz, Christina; Wallerius, Majken; Xie, Hanjing; Ullén, Anders; Harmenberg, Ulrika; Lidbrink, Elisabet; Rolny, Charlotte; Andersson, John; et al.
ABSTRACT: Regulatory T cells (Treg) suppress anti-tumor immune responses and their infiltration in the tumor microenvironment is associated with inferior prognosis in cancer patients. Thus, in order to enhance anti-tumor immune responses, selective depletion of Treg is highly desired. We found that treatment with zoledronic acid (ZA) resulted in a selective decrease in the frequency of Treg that was associated with a significant increase in proliferation of T cells and natural killer (NK) cells in peripheral blood of patients with metastatic cancer. In vitro, genome-wide transcriptomic analysis revealed alterations in calcium signaling pathways in Treg following treatment with ZA. Furthermore, co-localization of the nuclear factor of activated T cells (NFAT) and forkhead box P3 (FOXP3) was significantly reduced in Treg upon ZA-treatment. Consequently, reduced expression levels of CD25, STAT5 and TGFβ were observed. Functionally, ZA-treated Treg had reduced capacity to suppress T and NK cell proliferation and anti-tumor responses compared with untreated Treg in vitro. Treatment with ZA to selectively inhibit essential signaling pathways in Treg resulting in reduced capacity to suppress effector T and NK cell responses represents a novel approach to inhibit Treg activity in patients with cancer.